Corporate Social investment and development - Menzies, Gail (Department of Philosophy, 2014)
Can the Corporate Social Investment initiatives of small businesses contribute to development? Corporate Social Investment (CSI) and its counterpart Corporate Social Responsibility (CSR) are the terms used for the external and internal initiatives undertaken by companies to contribute to the upliftment of their stakeholders and communities. This research paper attempts to establish whether the CSI initiatives of small, local (Cape Town) companies have the potential to contribute to this upliftment or development. The literature review conducted on the relevant topic discovered three major arguments surrounding this debate. Firstly there are those authors that believe that CSI / CSR cannot contribute to development; secondly those authors that believe that CSI / CSR can contribute to development; and finally those authors that believe that more research on this topic is required before any such statements can be made. The outcome of the literature will reveal some issues surrounding this argument. They are: motivations, compatibility, implementation, business advantage, business and NGOs and community focus and research and sustainability. Following the establishment of the technical issues the paper will then propose that Amartya Sen's Development as Freedom theory be used to further investigate the development potential of CSI initiatives. Along with the technical suggestions, Sen's five 2 freedoms will be used to analyse whether any potential development successes can be observed from seven case studies. The freedoms are: political freedoms, economic facilities, social opportunities, transparency guarantees and protective security. Each of these can contribute to development. The case studies are CSI initiatives selected from local small businesses and the required information was extracted by means of an openended qualitative questionnaire. These case studies will be analysed against the freedoms and the discoveries from the literature review. The conclusions drawn show that some potential does exist for CSI initiatives. It also shows that Sen's Development as Freedom can be effectively applied to small scale projects at the micro level.